Multifunctional applications of NaGdF4:Ho3+/Yb3+ up-conversion phosphor synthesized via two different routes: a comparative study. (21st August 2019) - Kumar, A; Tiwari, S P; Kumar, K; Esteves da Silva, Joaquim C G
Abstract: Herein, the synthesis of Ho 3+ (2 mmol%)/Yb 3+ (18 mmol%) doped NaGdF4 up-conversion (UC) phosphor particles via two different chemical routes namely thermal decomposition (sample 1) and hydrothermal (sample 2) methods is done and then the structural and optical properties were studied. The properties of the samples are characterized via different techniques. The UC emission bands are obtained in the visible range at 488 nm, 543 nm, 645 nm and 754 nm wavelengths corresponding to 5 F3  →  5 I8, 5 F4 / 5 S2  →  5 I8, 5 F5  →  5 I8 and 5 I4  →  5 I8 transitions, respectively. The change in sample internal temperature due to the 980 nm diode laser excitation is calculated for both the samples. The variation in UC emission intensity as a function of the complete cycle of the applied magnetic field (0–1.1 × 10 4 Oe-0) is confirmed the optical bi-stability behavior of the present sample. Sample 1 has found a colloidal stable in water and hence this sample dispersed in the aqueous medium of polyvinyl alcohol (PVA) and thus utilized in security witting demonstration on a bank-note surface. Sample 2 with high emission intensity is demonstrated for latent fingermark detection.